Pengaruh Pendampingan Pengnalan Kesenian Jaranan Jombang di Situbomdo Sejak Dini pada Anak Berkebutuhan Khusus - Yulia Tutuik Nurfia; Suyanti Suyanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research raises the issue of the background of Jaranan Jombang (Jaran Dor) art and the function of Jaranan Jombang (Jaran Dor) art for children with special needs. This research aims to determine the background of Jaranan Jombang (Jaran Dor) in Jombang Regency for assisting parents who have children with special needs. The method used is a qualitative approach, while data collection uses observation, interview and documentation techniques. Based on research, the following are obtained. Jaranan Jombang (Jaran Dor) functions as a means of introducing art to parents who have children with special needs.